EXPRESSING FEELINGS THROUGH VISUAL WORKS: HUMILIATION, PRIDE AND CELEBRATION OF FOOTBALL FANS - Muhammad Robby Farhan; Indita Aprilia; Virienia Virienia (LPSDI Bina Patria, 2023)
Fans are an inseparable part of football. The presence of a fan is very important for a team during a match or not, even the presence of a fan can be felt even though they are not present directly during the match. Like physical clashes at live events, visual meme clashes also often occur on social media. All forms of emotional expression such as insults, pride, and celebrations are presented on social media. These various visual memes will be analyzed through semiotic analysis. By using Pierce's theory of semiotics, visual memes can be interpreted by the signs that exist in the visual meme itself. Through this theory, visual meme works become easier to interpret as an expression of the creator's feelings for something or a group of people. If interpreted correctly, visual meme works will have a positive impact and vice versa. With this visual meme creation among fans of European football clubs in Indonesia, it is hoped that there will be no more commotion between fans of European football clubs in Indonesia, who were previously known to be vocal, and even some unscrupulous fans who have anarchic nature.